Preliminary study on the effect of reduced graphene oxide, gold nanoparticles, and nafion® concentration on redox peak current for electrochemical biosensing - Ismail, Nur Alya Batrisya; Arris, Farrah Aida; Tumian, Afidalina; Wan Salim, Wan Wardatul Amani (Taylor's University, 2019)
Electrochemical characterization of graphene-based nanocomposites as transducer nanomaterial for highly sensitive biosensors was performed. Parameters that were varied include graphene oxide (GO) concentration, amount of added gold nanoparticles (AuNPs), and Nafion® as binder for enhancing electrical conductivity of the transducer layer. The nanocomposite-modified glassy carbon electrode (GCE) transducer layers were fabricated via a simple two-step drop-cast and subsequent electrochemical reduction. Cyclic voltammetry (CV) was used to characterize the redox capability of the transducer layer. Electrochemical deposition of ultra-highly concentrated single-layer graphene oxide (UHC GO) suspension with a concentration of 6 mg/ml gave highest anodic peak current Ipa,, ~0.6 mA, after electrochemical reduction, compared to most peak currents reported in the literature for an electrode with an inner diameter of 3 mm; adding UHC GO:AuNPs in a 2:1 ratio followed by electrochemical reduction resulted in even higher Ipa (0.4 mA higher) in comparison to reduced UHC GO alone, whereas adding UHC GO:Nafion® in an 8:1 ratio shows a 1-mA increase in peak current. Therefore, AuNPs and Nafion® can be added to reduce UHC GO as nanocomposite for the development of a redox-active transducer that can result in highly sensitive biosensors.